1986
DOI: 10.1079/bjn19860035
|View full text |Cite
|
Sign up to set email alerts
|

Studies on iron availability in man, using stable isotope techniques

Abstract: 1. Iron absorption from 10 mg Fe (as ferrous sulphate), labelled with 1.3 mg 58Fe, was measured in fasting, non-anaemic adult subjects by the faecal-balance technique. The measurement was performed twice, each subject being given, in random order, either 50 mg Fe or a placebo 18 h before the 58Fe-labelled FeSO,. 2.The 50 mg Fe load significantly reduced Fe absorption the following day (P < 0.01), from a mean of 35.4(SEM 4.6)% to 29.0 (SEM 5.1)%. This points to the importance of strict dietary control during Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
(7 reference statements)
1
24
0
Order By: Relevance
“…With the exception of our preliminary report concerning determination of 58Fe enrichment of erythrocytes by ICP/MS (2), studies of iron availability with stable isotopes have been based on determinations of fecal excretion of the isotope (8,9). Data presented herein suggest the feasibility of studies in which "Fe enrichment of erythrocytes rather than fecal excretion of "Fe serves as the endpoint.…”
Section: Discussionmentioning
confidence: 91%
“…With the exception of our preliminary report concerning determination of 58Fe enrichment of erythrocytes by ICP/MS (2), studies of iron availability with stable isotopes have been based on determinations of fecal excretion of the isotope (8,9). Data presented herein suggest the feasibility of studies in which "Fe enrichment of erythrocytes rather than fecal excretion of "Fe serves as the endpoint.…”
Section: Discussionmentioning
confidence: 91%
“…Anaemic animals had a higher efficiency of absorption than control animals, and giving a low-Fe diet for 3 d enhanced the capacity of the control but not the anaemic rats to absorb Fe. Stable isotope studies using 58Fe demonstrated that the mucosal effect was also seen in man 24 h after the administration of a placebo or a 50 mg Fe load, the mean absorption from a 10 mg dose of Fe being reduced by approximately 29% after the Fe load (Fairweather-Tait & Minski, 1986). This points to the necessity of strict dietary control during Fe absorption studies, to eliminate bias in the results, and indicates that lack of such control may be partly responsible for the large variation in absorption measured in human subjects of apparently similar status.…”
Section: Quantity In Dietmentioning
confidence: 99%
“…1969) which at present remain largely unexplained. Human subjects in Fe studies (Fairweather-Tait & Minski, 1986) show widely differing capacities for Fe absorption from a test dose of 58FeS04 after an overnight fast, although they apparently have a similar Fe status. This variation is probably linked to differences in body Fe status (Cooke et al 1974), gastric acid secretion (Jacobs et al 1964) and to other physiological factors at the time of dosing.…”
mentioning
confidence: 99%
“…The use of stable isotopes in mineral nutrition research is considered to be an important and valuable tool from the point of view that they have no exposure to radiation and no decay over time (1). Since 1963, the availability and metabolism of iron in man have been thoroughly studied through the standard method of fecal monitoring using 58Fe (2)(3)(4)(5)(6)(7). To date, there have been some calculation methods to determine the iron absorption (2,7).…”
mentioning
confidence: 99%